Peripheral sensitization is demonstrated in subacromial pain syndrome, with central sensitization found only in females. Issue 2 (16th May 2022) - King, Jacqlyn; Shapiro, Matthew; Karduna, Andrew
Abstract: The objective of this study was to explore whether hypersensitivity in patients with subacromial pain syndrome (SPS) manifests purely as localized peripheral sensitization or central sensitization, is influenced by the presence of subacromial pain, and presents similarly in male and female patients. Pressure pain threshold was assessed in both a patient cohort with unilateral SPS and an uninjured matched control group. Control subjects were assessed twice, with a 15 minute rest period between testing, while patients were assessed at baseline and after an almost instantaneous reduction in pain arising from an anesthetic injection in patients. Patients received a subacromial injection consisting of both anesthetics (3 cc of 2% lidocaine and 6 cc 0.5% Marcaine with Epinephrine) and a corticosteroid agent (1 cc DepoMedrol). Patients demonstrated hypersensitivity across the involved shoulder only, providing evidence for peripheral sensitization. There were trends for hypersensitivity across remote joints, however when separated by sex, only female patients demonstrated both peripheral and central sensitization. Immediate pain reduction had no influence on hypersensitivity in the short‐term. Clinical Significance: Neuropathic components are likely present in some patients with subacromial pain syndrome, and female patients may be particularly at risk for presenting with neuropathic pain. These findings are applicable towards understanding the heterogeneous etiology underlying subacromial pain syndrome and informing clinical management.